Behavior, Satisfaction, and Happiness in Joining the Open Chat Group's LINE Application Happy Money Happy Market by RMUTT - Sanont, Rujikarn; Yamakanith, Purinat; Suksawat, Sinittra (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
This research article aims to study service usage behavior, satisfaction, and compare happiness before and after usage LINE application open chat group of happy money happy market group by RMUTT. It is a quantitative research. Population are clients of LINE application open chat group of happy money happy market by RMUTT. The sample group are clients of the LINE application open chat group of happy money happy market by RMUTT aged 18 years and over. Non-probability sampling by using a convenient sampling method, there were 400 people. The research tool was a questionnaire. Statistics were descriptive statistics consisting of frequency, percentage, mean, standard deviation and the statistics to test the hypothesis is the Paired Sample t-test. The research results found that: clients use the open chat group at their convenient time, every day. The products that they purchase the most are everyday goods. The average cost per 1 purchase is 1,001-1,500 baht, the product was purchased for themselves and the person who has the most influence is friend. The satisfaction of usage the service is the highest level of satisfaction in terms of place or distribution channels followed by people or system administrator of the open chat group. The happiness before and after participation the application line open chat group found that there was a statistically significant difference at the level 0.01, the sample group was happier after participation. Article history: Received 6 March 2023 Revised 8 October 2023 Accepted 10 October 2023 SIMILARITY INDEX = 6.48 %